2014
DOI: 10.1038/nm.3483
|View full text |Cite
|
Sign up to set email alerts
|

Inverse agonist of estrogen-related receptor γ controls Salmonella typhimurium infection by modulating host iron homeostasis

Abstract: In response to microbial infection, expression of the defensin-like peptide hepcidin (encoded by Hamp) is induced in hepatocytes to decrease iron release from macrophages. To elucidate the mechanism by which Salmonella enterica var. Typhimurium (S. typhimurium), an intramacrophage bacterium, alters host iron metabolism for its own survival, we examined the role of nuclear receptor family members belonging to the NR3B subfamily in mouse hepatocytes. Here, we report that estrogen-related receptor γ (ERRγ, encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
135
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 128 publications
(140 citation statements)
references
References 24 publications
5
135
0
Order By: Relevance
“…Like many other nuclear receptors, the activities of ERR␣ and ERR␥ can be modulated by available small-molecule ligands (C29, XCT790, GSK5182, GSK4716, etc.) (68)(69)(70)(71). Future efforts to test ERR␣ and ERR␥ ligands in animal models or even clinical settings of cardiac disease will help uncover their therapeutic values.…”
Section: Discussionmentioning
confidence: 99%
“…Like many other nuclear receptors, the activities of ERR␣ and ERR␥ can be modulated by available small-molecule ligands (C29, XCT790, GSK5182, GSK4716, etc.) (68)(69)(70)(71). Future efforts to test ERR␣ and ERR␥ ligands in animal models or even clinical settings of cardiac disease will help uncover their therapeutic values.…”
Section: Discussionmentioning
confidence: 99%
“…The ERR isoforms are primarily expressed in several organs, such as the heart, brain, kidney, pancreas, and liver (16,17). Recently, studies have shown that ERRg is involved in metabolic diseases such as type 2 diabetes mellitus, alcohol-induced oxidative stress, liver injury, and microbial infection through impaired hepatic gluconeogenesis (18,19), hepatic insulin signaling (20), and iron metabolism (21).…”
mentioning
confidence: 99%
“…They are primarily expressed in tissues such as the heart, brain, kidney, pancreas, placenta, and liver [2], and are known to play a pivotal role in the development of diseases such as cancer and various metabolic disorders [3]. Among the ERRs, ERRγ in particular has been shown to be involved in metabolic diseases such as type 2 diabetes mellitus, alcohol-induced oxidative stress, liver injury, and microbial infections caused by impaired hepatic gluconeogenesis [4,5], impaired hepatic insulin signaling [6], and impaired iron metabolism [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence have revealed that the ERRγ inverse agonist 4 alleviates diabetes through the inhibition of hepatic gluconeogenesis in a PGC-1α-dependent manner [5]. Additionally, 4 has antimicrobial effects by reducing ERRγ-mediated hepcidin mRNA expression [7]. More recently, it was reported that 4 enhances the responsiveness of radioiodine therapy by modulating sodium iodide symporter (NIS) function in ATC cells via the regulation of ERRγ and the MAP kinase signaling pathway [12].…”
Section: Introductionmentioning
confidence: 99%